Burden of non-tuberculous mycobacterial pulmonary disease in Germany. Issue 4 (27th April 2017) - Diel, Roland; Jacob, Josephine; Lampenius, Niklas; Loebinger, Michael; Nienhaus, Albert; Rabe, Klaus F.; Ringshausen, Felix C.
The objective of this study was to estimate the burden of disease in incident patients with non-tuberculous mycobacterial pulmonary disease (NTM-PD). A sample of 7 073 357 anonymised persons covered by German public statutory health insurances was used to identify patients with NTM-PD. In total, 125 patients with newly diagnosed NTM-PD in 2010 and 2011 were matched with 1250 control patients by age, sex and Charlson Comorbidity Index, and followed for 39 months. The incidence rate for NTM-PD was 2.6 per 100 000 insured persons (95% CI 2.2–3.1). The mortality rate for patients with NTM-PD and the control group in the observational period was 22.4% and 6%, respectively (p<0.001). Mean direct expenditure per NTM-PD patient was €39 559.60 (95% CI 26 916.49–52 202.71), nearly 4-fold (3.95, 95% CI 3.73–4.19) that for a matched control (€10 006.71, 95% CI 8907.24–11 106.17). Hospitalisations were three times higher in the NTM-PD group and accounted for 63% of the total costs. Attributable annual direct costs and indirect work-loss costs in NTM-PD patients were €9093.20 and €1221.05 per control patient, respectively. Only 74% of NTM-PD patients received antibiotics and nearly 12% were prescribed macrolide monotherapy. Although NTM-PD is considered rare, the attributable mortality and financial burden in Germany are high. Efforts to heighten awareness of appropriate therapy are urgently needed. Newly diagnosed NTM-PD causes substantial healthcare costs and has high mortality http://ow.ly/Y0I03089UBc